Good night and good luck : live from Broadway [videorecording (DVD)] - Clooney, George; Brandt, Mac, 1980-; Dagger, Will; Denham, Christopher; Fleshler, Glenn (Magnolia Home Entertainment, 2025)
George Clooney's Tony-nominated, box-office record-breaking Broadway play chronicling a time in American history when legendary newsman Edward R. Murrow took an on-air stand against a growing tide of fearmongering and disinformation-and won.